2021
DOI: 10.3389/fmed.2021.747348
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Associated With the Motivation of Clinical Pharmacists: A Focus on the South African Context

Abstract: Introduction: Pharmacy practice in many middle to low-income countries has slowly transitioned from being product-focused to a more patient-focused clinical practice. Lack of motivation is one of the factors contributing to the scarcity of pharmacists in the wards. As little is known about motivation in clinical pharmacists, this study aimed to obtain insight into the quantity and quality of their work motivation and factors associated with it.Methods: Self-determination Theory, used as the framework, describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Work environments in which collegial support is received motivates clinical pharmacists and improves their wellbeing. This supports the implementation of clinical services, prevents possible adverse events (burnout) and keeps the quality of patient care as high as possible [ 18 ]. Knowledge, attitude and perceptions of other HCPs towards the role of the clinical pharmacist are important factors that can either facilitate or hinder the implementation and expansion of clinical pharmacy services [ 5 , 13 , 14 , 19 ].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Work environments in which collegial support is received motivates clinical pharmacists and improves their wellbeing. This supports the implementation of clinical services, prevents possible adverse events (burnout) and keeps the quality of patient care as high as possible [ 18 ]. Knowledge, attitude and perceptions of other HCPs towards the role of the clinical pharmacist are important factors that can either facilitate or hinder the implementation and expansion of clinical pharmacy services [ 5 , 13 , 14 , 19 ].…”
Section: Introductionmentioning
confidence: 92%
“…Among individuals not appointed in dedicated clinical pharmacy positions, higher amotivation (lack or absence of motivation) for delivering clinical pharmacy services were found. These pharmacists did not feel supported and related to other HCPs, compared to those in dedicated positions [ 18 ]. If allocated more ward-based time, the majority of pharmacists in a study by Bronkhorst et al, felt that they can improve the rational use of medication.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that among South African clinical pharmacists, higher motivation to work is found in graduates who do not practice as a clinical pharmacist, as well as in graduates who do not receive additional financial benefits for clinical services [16]. In turn, among hospital pharmacists of the specialized hospital Tikur Anbesa (Addis Ababa, Ethiopia), 53.0 % of respondents were satisfied with their work [17].…”
Section: Introductionmentioning
confidence: 99%
“…Training of clinical pharmacists in SA includes a Master's degree in clinical pharmacy. This was originally initiated in 2000 by one University, who graduated around 114 students since (Crafford et al, 2021). Four other universities followed, however not with a modular Master's degree, and graduated much less students (around 18).…”
Section: Introductionmentioning
confidence: 99%
“…Rhodes University offered a PharmD programme (Gous and Schellack, 2014), who graduated around 16 students before discontinuing the course. The slow uptake of clinical pharmacy services can be related to infrastructure and resource limitations (Crafford et al, 2021).…”
Section: Introductionmentioning
confidence: 99%